Opportunities for Implementing Alternative Dispute Resolution (ADR) in Settlement of Tax Disputes in Indonesia - Ebenezer Hutagalung; Zainal Mutaqqin; Muhamad Amirulloh (Dinasti Research, 2025)
The emergence of tax disputes as a consequence of differences in interests between tax authorities and taxpayers is a normal thing to happen. However, if an excessive number of tax disputes occur, this has the potential to create legal uncertainty, both for taxpayers and tax authorities. In theory and practice, a dispute resolution mechanism has developed as an implementation of law enforcement outside of court (non-litigation), namely a form of dispute resolution using the services of a neutral third party without going through a court process agreed upon by the parties. Indonesia already has provisions regarding dispute resolution outside of court, as stated in Law Number 30 of 1999, concerning Arbitration and Alternative Dispute Resolution, but this is only limited to civil and business cases or disputes. However, there is an opportunity to apply ADR in resolving public disputes, especially tax disputes, provided that ADR is limited to administrative efforts and does not conflict with legislation, as well as legal updates at the level of the Act regarding the implementation of ADR. The opportunity to apply ADR to tax (administrative) disputes can be carried out during the discussion of audit results by the Quality Assurance (QA) team when there is no common ground between the tax auditor and the Taxpayer. The QA team can act as an independent and impartial mediator whose decisions are binding. The decision of the QA team as a mediator is also a preventive effort to prevent tax disputes from arising.